Fluctuation in Aridity Over RajasthanAnd Neighbour Hood - Parthasarathy, B; Rakhecha, P (Annals of Arid Zone, 2016)
The nature of fluctuations in the aridity over 12 representative stations of Rajasthan and its neighborhood during the past 65 years (1901-1965) have been discussed. The power spectrum analysis reveals the presence of significant quasi-biennial oscillation and periodicities somewhat paralleling the sunspot cycle at Delhi and Barmer.